Prevalence and Smoking Behavior Characteristics of Nonselected Smokers With Childhood and/or Adult Self-Reported ADHD Symptoms in a Smoking-Cessation Program: A Cross-Sectional Study. (April 2015) - Fond, Guillaume; Guillaume, Sebastien; Jaussent, Isabelle; Beziat, Severine; Macgregor, Alexandra; Bernard, Paquito; Courtet, Philippe; Bailly, Daniel; Quantin, Xavier
Background: ADHD involves impairing core symptoms of inattention and hyperactivity/impulsivity in children (childhood ADHD = CH) that may persist in adulthood (adult ADHD = AD). Conflicting findings have been found regarding AD prevalences among adult smokers, and it is unclear whether AD is associated with a more severe smoking behavior in adulthood.Objective: The aim of this article is (a) to determine CH and AD prevalences in a nonselected sample of adult smokers, (b) to describe the characteristics of smokers with ADHD symptoms versus those without, and (c) to determine whether CH and/or AD symptoms are risk factors for more severe smoking in adulthood.Method : Three hundred and seventy-three participants aged 18 years and over were prospectively recruited in a smoking-cessation unit. Participants were classified as "no ADHD symptoms, " "CH symptoms, " or "AD symptoms" according to their baseline score on the Wender Utah Rating Scale (WURS) alone (for CH symptoms) and WURS combined to the Adult Self Report Scale (ASRS) for AD symptoms. Other clinical variables were reported at first consultation.Results: (a) CH symptoms were reported in 15.3% (57/373) of the total sample, 42.1% (24/57) of whom also had persistent ADHD symptoms in adulthood (prevalence of AD was 24/373 = 6.4%). (b) In comparison with participants without ADHD symptoms, smokers with ADHD symptoms consume significantly more tobacco, but ADHD symptoms were no longer significantly associated with the daily number of smoked cigarettes after adjustment for sociodemographic variables. No significant association was found between the two groups and age at the first cigarette, age at onset daily smoking, and nicotine dependence. (c) Participants were categorized into three groups: Group 1 without ADHD symptoms lifetime (NH; n = 316), Group 2 with childhood history of ADHD symptoms (CH; n = 33), and Group 3 with Adult ADHD symptoms (AD; n = 24). The association with tobacco consumption (>20 cigarettes/day) was significant for CH only ( p = .02). After adjustment for gender, age, professional status, and educational level, this association was not longer significant.Conclusion: Childhood and adult ADHD symptoms are both highly prevalent among nonselected smokers but our study failed to show more severe smoking characteristics among these participants after adjustment with sociodemographic variables.